Isolation and culture of protoplasts from the medicinal plants Centella asiatica - Zaleha A. Aziz; Davey, M. R.; Lowe, K. C.; Power, J. B. (Sociedade Brasileira de Plantas Medicinais, 2006)
In the present investigation, protoplasts were isolated from cell suspensions initiated from leaf laminae and petioles using an enzyme mixture consisting of 1.5% (w/v) Cellulase R10, 1.0% (w/v) Macerozyme R10 and 0.5% (w/v) Driselase in CPW salts solution with 13% (w/v) mannitol as osmotic stabilizer. Yields and viabilities of isolated protoplasts were 1.2 x 105 ± 0.1 g-1 fresh weight and 20.8 ± 4.4% for protoplasts from lamina-derived cell suspensions and 7.9 x 105 ± 1.5 g-1 fresh weight and 79.3 ± 13.4% for protoplasts from petiole-derived cell suspensions. Protoplasts from lamina explant-derived cell suspensions were cultured at plating densities of 0.25 x 105 – 2.0 x 105 protoplasts ml-1 in half-strength B5 based medium containing 0.1 mgl-1 2,4-dichlorophenoxyacetic acid (2,4-D) and 0.3 mgl1 zeatin, dispensed as semi-solid agarose droplets (each approx. 70 µl in volume) in 5.5 cm diameter Petri dishes (10 droplets per dish). First mitotic divisions of protoplast-derived cells were observed after 4 d of culture at an optimum plating density of 0.5 x 105 protoplasts ml-1, giving an initial plating efficiency at this time of 12.7 ± 0.6%. After 42 d of culture, protoplast-derived cell colonies were creamy-white in colour and each approx. 1 mm in diameter, with a final plating efficiency of 0.6 ± 0.2%. Cell colonies transferred to semi-solid proliferation medium containing 2,4-D (4.0 mgl-1) and zeatin (0.2 mgl-1) were creamy-yellow in appearance, whereas colonies cultured on medium devoid of these growth regulators became light green and compact. In the case of protoplasts from petiole-derived cell suspensions, culture in Murashige and Skoog (1962)-based medium supplemented with 2.0 mgl-1 alpha-naphthaleneacetic acid and 0.5 mgl-1 6-benzylaminopurine resulted in an initial plating efficiency of 19.3 ± 4.2% at an optimum plating density of 1.0 x 105 protoplasts ml-1. However, mitotic division was not sustained after this stage. Plant regeneration studies are on-going from protoplasts isolated from lamina-derived cell suspensions.